Relationship Between Job Satisfaction with Intention to Turnover: A Study on Malaysia France Institute - See, Brian Mei Chiat (1999)
The purpose of this study is to identify the relationship between job satisfaction with turnover intentions of Malaysia France Institute employees. The instrument employed was the Minnesota Satisfaction Questionnaire (MSQ) (Weiss et al., 1967) to measure job satisfaction, and a four-items adapted from Hunt, Osborn and Martin ( 198 1) was used to measure intention to turnover. The Pearson correlation, T -test, and ANOVA test were used to determine the relationships and differences between variables. A total of 130 self-administered questionnaire was distributed to all MFI employees and 72 (55. 38%) responses were collected. The results showed that more than half (55. 6%) of MFI employees were either satisfied or very satisfied with their current job and only 5. 6% have low job satisfaction. The main job satisfiers in MFI were the job activity and relationship among co-workers. Meanwhile the main job dissatisfiers were company policy and practices, and job advancement. Though it was found that job satisfaction has a moderate negative relationship (r=-0.397, p<0.0 1) with overall intention to turnover, the intention to turnover in MFI was high too. Only 8.3% respondents have low turnover intention, while 30.6% have high turnover intention and the other 6 1. 1 % have moderate turnover intention level. Other findings obtained like age, salary and working tenure did not have any significant relationship with both job satisfaction and turnover intention. Job satisfaction and intention to turnover also did not differ by gender and academic qualification. The analysis confirms that the measures of job satisfaction exert an inverse relationship with intention to turnover. That is, the higher levels of job satisfaction are associated with lower levels of intention to turnover. However, the situation in MFI was a little different, where high level of job satisfaction does not guarantee low intention to turnover. The probable reason behind the finding was that though the MFI employees are satisfied with their current job, they perceive that there are better job opportunities available elsewhere.